EVALUASI PELAYANAN KAWASAN PASAR 16 ILIR PASCA KEBIJAKAN PENERTIBAN DAN TATA KOTA PALEMBANG TAHUN 2004 - Rizky Pratama Rhomadona; Muhammad Imam Akbar Hairi; Amaliatulwalidain Amaliatulwalidain (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
The focus of this study is the evaluation of the service area of post-market 16 Ilir Palembang city planning discipline policy. There are several permasalhan the background of these researchers are still many of them street vendors, illegal parking, public transportation buildup waiting for passengers at sembanrang place, extortion, high rates of kriminalisme and lack of presence of public toilets as a means of support available. The purpose of this study is the formulation of the problem of how the evaluation region 16 Ilir market order and governance policies after the city of Palembang. The research method used in this research is descriptive quantitative data collection techniques done is through a literature review, interviews with select competent informants and questionnaires to 100 respondents to get the data properly. Data were obtained and then analyzed quantitatively. From the research shows that exercising pelayang in 16 Ilir market area will be undertaken after the planning policy has not undergone a change that can be felt by the community as much as possible. It is seen from wawancar and results of questionnaires that indicate that indeed there has been no changes that are so significant to the arrangement in kawasana 16 Ilir market in Palembang. Keywords : Evaluation, Public Services, City Planning